2023
DOI: 10.3389/fpsyg.2023.1157644
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress imparts a transient benefit to task-switching that is not modulated following a single bout of exercise

Abstract: IntroductionCognitive flexibility represents a core component of executive function that promotes the ability to efficiently alternate—or “switch”—between different tasks. Literature suggests that acute stress negatively impacts cognitive flexibility, whereas a single bout of aerobic exercise supports a postexercise improvement in cognitive flexibility. Here, we examined whether a single bout of aerobic exercise attenuates a stress-induced decrement in task-switching.Materials and MethodsForty participants (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
0
2
Order By: Relevance
“…This further supports our assumption of the linkage between OSE and executive function. However, the opposite result was shown in a previous study [ 65 , 66 ]. Morava et al [ 65 ] found no effect after a single bout of aerobic exercise in task-switching performance under pressure situations.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This further supports our assumption of the linkage between OSE and executive function. However, the opposite result was shown in a previous study [ 65 , 66 ]. Morava et al [ 65 ] found no effect after a single bout of aerobic exercise in task-switching performance under pressure situations.…”
Section: Discussioncontrasting
confidence: 88%
“…However, the opposite result was shown in a previous study [ 65 , 66 ]. Morava et al [ 65 ] found no effect after a single bout of aerobic exercise in task-switching performance under pressure situations. Based on the research of effect size, there is still no conclusion about whether single-bout exercise can effectively acutely improve people’s executive function.…”
Section: Discussioncontrasting
confidence: 88%